2011
DOI: 10.1136/adc.2011.212563.137
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of overweight-obesity in children - are paediatricians missing the opportunity in outpatient clinics?

Abstract: Aims Overweight-obesity is an emerging major health issue in children in the UK. Success of any initiative to address this and mitigate its potential health burden during adulthood relies on proactive engagement of children, parents and professionals. Paediatricians will naturally be at the forefront of such interventions. This study explores if opportunities available in children's outpatient clinics are utilised effectively. Methods This retrospective study looked at 1000 data-sets (routine height and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is surprising and may represent under‐recognition of obesity in children, which has been reported in up to 83% of children with overweight and 44% of children with obesity . Other studies have also demonstrated under‐recognition of obesity by parents of children with overweight, particularly younger children compared with adolescents and African American parents compared with White parents .…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising and may represent under‐recognition of obesity in children, which has been reported in up to 83% of children with overweight and 44% of children with obesity . Other studies have also demonstrated under‐recognition of obesity by parents of children with overweight, particularly younger children compared with adolescents and African American parents compared with White parents .…”
Section: Discussionmentioning
confidence: 99%
“…10 There is also some evidence on practices, attitudes and training needs of Australian primary care nurses surrounding child obesity prevention in the general practice setting. 11 12 In the UK, Gali et al 13 suggested that paediatricians are missing an opportunity in outpatient clinics to identify and intervene in children who are overweight. Their 2011 study reported that 25% of girls and 29% of boys were overweight or obese, but that 83% of overweight children were unrecognised as BMI was not routinely calculated, despite availability of height and weight data.…”
Section: Introductionmentioning
confidence: 99%